Acigol rhyolite field, Central Anatolia (part 1): high-resolution dating of eruption episodes and zircon growth rates - Schmitt, A.; Danisik, Martin; Evans, Noreen; Siebel, W.; Kiemele, E.; Aydin, F.; Harvey, J. (Springer, 2011)
Protracted pre-eruptive zircon residence is frequently detected in continental rhyolites and can conflict with thermal models, indicating briefer magma cooling durations if scaled to erupted volumes. Here, we present combined U-Th and (U-Th)/He zircon ages from the Acigol rhyolite field (Central Anatolia, Turkey), which is part of a Quaternary bimodal volcanic complex. Unlike other geochronometers, this approach dates crystallization and eruption on the same crystals, allowing for internal consistency testing. Despite the overall longevity of Acigol rhyolite volcanism and systematic trends of progressive depletion in compatible trace elements and decreasing zircon saturation temperatures, we find that zircon crystallized in two brief pulses corresponding to eruptions in the eastern and western part of the field during Middle and Late Pleistocene times, respectively. For Late Pleistocene zircon, resolvable differences exist between interior (average: 30.7 ± 0.9 ka; 1r error) and rim (21.9 ± 1.3 ka) crystallization ages. These translate into radial crystal growth rates of *10-13 to 10-14 cm/s, broadly consistent with those constrained by diffusion experiments. Rim crystallization and (U-Th)/He eruption ages (24.2 ± 0.4 ka) overlap within uncertainty. Evidence for brief zircon residence at Acigol contrasts with many other rhyolite fields, suggesting that protracted zircon crystallization in, or recycling from, long-lived crystal mushes is not ubiquitous in continental silicic magma systems. Instead, the span of pre-eruptive zircon ages is consistent with autochthonous crystallization in individual small-volume magma batches that originated from basaltic precursors.